Development and validation of an online emotional intelligence training program - Durham, Michelle R. Persich; Smith, Ryan; Cloonan, Sara; Hildebrand, Lindsey L.; Woods-Lubert, Rebecca; Skalamera, Jeff; Berryhill, Sarah M.; Weihs, Karen L.; Lane, Richard D.; Allen, John J. B.; Dailey, Natalie S.; Alkozei, Anna; et al. (Frontiers in Psychology, 2023)
Introduction Emotional intelligence (EI) is associated with a range of positive health, wellbeing, and behavioral outcomes. The present article describes the development and validation of an online training program for increasing EI abilities in adults. The training program was based on theoretical models of emotional functioning and empirical literature on successful approaches for training socioemotional skills and resilience. Methods After an initial design, programming, and refinement process, the completed online program was tested for efficacy in a sample of 326 participants (72% female) from the general population. Participants were randomly assigned to complete either the EI training program (n = 168) or a matched placebo control training program (n = 158). Each program involved 10-12 hours of engaging online content and was completed during either a 1-week (n = 175) or 3-week (n = 151) period. Results Participants who completed the EI training program showed increased scores from pre- to post-training on standard self-report (i.e., trait) measures of EI (relative to placebo), indicating self-perceived improvements in recognizing emotions, understanding emotions, and managing the emotions of others. Moreover, those in the EI training also showed increased scores in standard performance-based (i.e., ability) EI measures, demonstrating an increased ability to strategically use and manage emotions relative to placebo. Improvements to performance measures also remained significantly higher than baseline when measured six months after completing the training. The training was also well-received and described as helpful and engaging. Discussion Following a rigorous iterative development process, we created a comprehensive and empirically based online training program that is well-received and engaging. The program reliably improves both trait and ability EI outcomes and gains are sustained up to six months post-training. This program could provide an easy and scalable method for building emotional intelligence in a variety of settings.